Unexpectedly long progression-free time in a patient with squamous cell carcinoma of the lung treated with Nivolumab – a case study - Szklener, Katarzyna; Piwowar, Klaudia; Klas, Jakub; Kluz, Natalia; Mańdziuk, Sławomir (Journal of Education, Health and Sport, 2022)
Background: In the reported case, our patient with lung cancer diagnosed as squamous cell carcinoma (SqCC) achieved eight times longer progression-free time (PFT; 25.3 months) than that obtained in the median of randomized clinical trials (3.5 months). Case Report: A 61-year-old man presented for treatment due to a long-lasting cough and a type of pain in the chest, in good general condition. The patient had a smoking history when he was young. Computed tomography (CT) showed a lesion larger than 70 x 60 mm. The diagnosis was made on the basis of the bronchoscopic material. The prognosis was unfavorable and the tumor was inoperable. In the first line of treatment, chemotherapy with cisplatin was started. Due to the progression, second-line immunotherapy with Nivolumab was administered, and was continued for a longer period of time. Treatment was well tolerated and there were no side effects reported. Therapy was however interrupted due to the patient's deteriorating condition and progression in the follow up CT examination. Finally the patient was qualified for palliative treatment with chemotherapy and zoledronic acid. Opioid medications were used to treat pain. Conclusion: The patient lived for over 4 years, including over 2 years without progression. It therefore seems that there is a group of patients who respond exceptionally well to immunotherapy, but the identification of predictors requires further research.